Preventing treatment abandonment for children with solid tumors: A single‐center experience in Brazil. Issue 7 (2nd April 2019) - Ferman, Sima; Lima, Fernanda Ferreira da Silva; Lage, Carollyne Rodrigues Souza; da Hora, Senir Santos; Vianna, Danielle Tavares; Thuler, Luiz Claudio
Abstract: Background: High rates of treatment abandonment have been considered one of the major limitations to achieving high cure rates of childhood cancer in developing countries. The aims of this study were to report the prevalence and factors associated with treatment abandonment for children diagnosed with solid tumors in one reference center in Brazil and to describe effective strategies to prevent it. Procedures: A retrospective review was conducted using data from 1139 children (0–18 years) treated for solid tumors at the Brazilian National Cancer Institute, during the period between January 2012 and December 2017. Treatment abandonment was defined as recommended by the International Society of Pediatric Oncology. The impact of implementing a patient‐tracking system was evaluated. Descriptive statistics were used to analyze patient characteristics. Chi‐square test was used for statistical analysis, with the significance level <0.05. Results: Of 1139 patients, 1.66% refused or abandoned treatment. Although from 2012 to 2013 there was an increase in the abandonment rate, it then decreased by 63.8% from 2013 to 2017 (2.5% to 0.9%). In the multivariate model, only retinoblastoma diagnosis was associated with abandonment (odds ratio = 5.0; 95% confidence interval, 1.2–20.4; P = 0.025). In our cohort, abandonment rates were not associated with increased death. Conclusion: Monitoring missed appointments, and early interventions to address issues associated with providing resources to help families during treatment were effective in achieving very low abandonment rates.